Design and Climate-Responsiveness Performance Evaluation of an Integrated Envelope for Modular Prefabricated Buildings. (7th August 2018) - Li, Junjie; Lu, Shuai; Wang, Wanlin; Huang, Jie; Chen, Xinxing; Wang, Jiayi
Abstract : Modular prefabricated buildings effectively improve the efficiency and quality of building design and construction and represent an important trend in the development of building industrialization. However, there are still many deficiencies in the design and technology of existing systems, especially in terms of the integration of architectural performance defects that cannot respond to occupants' comfort, flexibility, and energy-saving requirements throughout the building's life cycle. This research takes modular prefabricated steel structural systems as its research object and sets the detailed design of an integrated modular envelope system as the core content. First, the researcher chose two types of thermal insulation materials, high insulation panels and aerogel blankets, in order to study the construction details of integrated building envelopes for modular prefabricated buildings. Focusing on the weakest heat point, the thermal bridge at the modular connection point, this work used construction design and research to build an experimental building and full-scale model; the goal was to explore and verify the feasibility of the climate-responsive construction technique called "reverse install." Second, as a response to climate change, building facades were dynamically adjusted by employing different modular building envelope units such as sunshades, preheaters, ventilation, air filtration, pest control, and other functional requirements in order to improve the building's climate adaptability. Finally, based on the above structural design and research, this study verified the actual measurements and simulation, as well as the sustainability performance of the structure during the operational phase, and provided feedback on the design. The results highlight the environmental performance of each construction detail and optimized possibilities for an integrated envelope design for modular prefabricated buildings during both the design and renovation phases.